Vehicle Domain-Specific Language: Unifying Modeling and Code Generation for Low-Code Automotive Development - Liao, Lei; Wang, Junjie; Xu, Zhensheng; Mu, Fangwen; Yang, Yukun (IEEE/ACM International Conference on Automated Software Engineering : [proceedings], 2024)
The automotive industry is undergoing rapid growth driven by advancements such as electrification, necessitating efficient software development methodologies. While model-based system engineering is prevalent in automotive software development, its application is typically confined to the requirements and design phases, with manual coding still dominating the development process, resulting in extended development efforts and cycles. To address these challenges, we propose Vehicle Domain-Specific Language (VDSL), a low-code development tool that integrates modeling and automatic code generation. With VDSL, users can simply specify their requirements and utilize graphical drag-and-drop along with parameter configuration to efficiently implement vehicle functionality with auto-generated code. Tested and evaluated on 3 vehicle models across 18 months at GAC Group, VDSL has demonstrated its effectiveness in significantly reducing development effort and costs, improving resource efficiency, and providing greater flexibility for system updates via Over-The-Air (OTA) Technology. This work further enhances the practicality of model-based development in the automotive domain, boosting development efficiency and potentially enhancing quality.